The effect of a mental training program on anxiety levels (disabled and general) among football players participating in school sports competitions - Boureghda Mohamed, Messaoud; mhimdat, rachid (sports creativity, 2025)
This study aimed to identify the effect of a proposed mental training program on anxiety levels—specific, general, and specific—among students enrolled in the Ibn Badi High School team in Constantine. The proposed mental training program consisted of 21 sessions over a period of 34 weeks. The researchers also utilized an anxiety scale developed by Mohamed Hassan Alaoui, based on the Achievement Anxiety Test. The researchers employed an experimental design with a sample of 22 players in the experimental group and 22 players in the control group. The researchers found statistically significant differences in anxiety levels between the control and experimental groups, favoring the experimental group. In conclusion, the researchers recommend incorporating mental training as a crucial aspect of athlete preparation, on par with physical, technical, and tactical preparation.